Agrochemical Description of Colmatage Soils Formed in Isfayramsoy Cone Spread - Sotiboldieva Gozalkhan Tolibjonovna B.F.F.D(PhD); Sodikova Zabida Tolkinovna (Zien Journals, 2023)
The article presents the agrochemical description of colmatage pale gray soils formed in the Isfayramsoy cone spread, in which the total nitrogen is 0.015-0.11% in the case where humus is 1.20-1.31% in plowed layers
Keywords: colmatage; humus; nitrogen